Analysis of the Marketing Mix of Tofu Products in Home Industry, Palangga District, South Konawe Regency (Case Study on Home Industry in Mekar Sari Village) - adi pratama, setiawan; Sarinah, Sarinah; Sakir, Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to determine the marketing mix of tofu products in the home industry in Mekar Sari Village, Palangga District, Konawe Selatan Regency. This research was conducted in Palangga Subdistrict, Konawe Selatan District. The subjects in this study were tofu processing business owners and 20 respondents of consumer respondents. While the object of this research is the Marketing Mix of Tofu Products in the Home Industry in Mekar Sari Village, Palangga District, Konawe Selatan Regency. The results showed that regarding the marketing mix analysis of tofu making business in Palangga Subdistrict, Konawe Selatan Regency it can be concluded that, the marketing mix (product, price, and place) has a very good category, this is in accordance with consumer ratings where 100% of respondents gave a high rating category based on class interval calculations. While the promotion mix has an unfavorable category, this is in accordance with consumer ratings where (60%) of respondents rated medium categories based on class interval calculations